KAPABILITAS DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PEKANBARU DALAM MENGELOLA DRAINASE DI KOTA PEKANBARU TAHUN 2023-2024 - Permana, Tio Dwiyan; ,, Muchid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study discusses the capability of the Public Works and Spatial Planning Office (PUPR) of Pekanbaru City in managing drainage within the city during 2023–2024. The study employs a descriptive qualitative method with data collection techniques consisting of document analysis, field observation, and interviews with relevant stakeholders within the PUPR Office. The theoretical framework used in this research is Leonard-Barton’s (1992) concept of Core Capabilities, which includes four main dimensions: Knowledge and Skills, Technical Systems, Managerial Systems, and Values and Norms. The results of the study indicate that the capability of the Public Works and Spatial Planning Office of Pekanbaru City in managing drainage remains reactive. Several obstacles were identified, including limited budget allocation, insufficient technical expertise of human resources, low community awareness regarding drainage cleanliness, and weak coordination between divisions within the PUPR Office. This research concludes that drainage governance in Pekanbaru has not yet operated optimally, as the current approach predominantly focuses on short term operational actions rather than strategic, data-driven planning. Therefore, integrating information technology, improving human resource capacity, increasing budget allocation, and strengthening community participation are essential strategies to achieve modern, efficient, and sustainable drainage governance. Keywords : Capabilities, Public Works and Public Housing Agency, Drainage Management, Pekanbaru City.